The Effect Of Rice Processing Optimization On Improving Production Management In Farmer Groups In Lauru Fadoro Village, Afulu District, North Nias Regency - Lase, Ranto Riston; Zai, Kurniawan Sarototonafo; Bate'e, Maria Magdalena; Bu'ulolo, Nanny Artatina (Universitas Dehasen Bengkulu, 2025)
This study uses quantitative research which aims to determine the effect of rice processing optimization on increasing production management in farmer groups in Lauru Fadoro Village, Afulu District, North Nias Regency. The method in this study uses a quantitative method, with the data analysis technique used is simple linear regression, the population in this study were members of farmer groups totaling 40 heads of families and a sample of 40 respondents. The test results show that for the results of the hypothesis test, the t-count value is 20,595 with a significant value of 0.000. Where the significance limit is 0.05 with a t table value of 2,024 which indicates that the calculated t value> t table (20,595> 2,024) which means that Ha is accepted and Ho is rejected. So it can be concluded that there is an effect of rice processing optimization on improving production management in farmer groups in Lauru Fadoro Village, Afulu District, North Nias Regency. And for the R Square determination coefficient test (R2), a value of 0.918 was obtained which was then entered into the formula KD = r2 x 100% or KD = 0.918 x 100% = 91.8%. So that the effect of rice processing optimization on improving production management is 91.8% and the remaining 8.2% are variables that are not examined or have no effect in this study.